Water-based polyhydroxy phenolic resin for preparing environment-friendly dipping solution and preparation method of water-based polyhydroxy phenolic resin

By using water-based polyhydroxyphenol resin, the problems of poor stability of raw materials in the RFL glue system and the existing environmentally friendly glue system are solved, and the preparation of environmentally friendly glue solution with simple process, environmentally friendly raw materials and non-toxicity is achieved, and the adhesion effect reaches the level of traditional RFL.

CN119708397AActive Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411867795.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The formaldehyde and resorcinol used in the existing RFL impregnation system are toxic, and the existing environmentally friendly impregnation system has poor stability and complex processes, which cannot meet the needs of industrial applications.

Method used

Using aqueous polyhydroxyphenol resin, it is prepared from phlogenetol and dialdehyde through specific preparation methods to form an environmentally friendly impregnation liquid. The method includes dissolving phthalocyanol in deionized water, adjusting the pH to 5 to 6, then adding dialdehyde compounds dropwise, controlling the viscosity of the reaction solution, and finally adjusting the pH to 7 to 8, and preparing an aqueous polyhydroxyphenol resin with a solid content of 5 to 13%.

Benefits of technology

The toxicity problem of raw materials in the RFL glue-impregnation system was overcome, and the prepared aqueous polyhydroxy phenolic resin had good viscosity and solid content control, the product structure was controllable, the repetitiveness was high, and there were many active groups, which was conducive to the link with fibers and rubbers, achieving a similar bonding effect as traditional RFL.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005194907780000071
    Figure BDA0005194907780000071
  • Figure BDA0005194907780000081
    Figure BDA0005194907780000081
  • Figure BDA0005194907780000082
    Figure BDA0005194907780000082
Patent Text Reader

Abstract

The invention belongs to the technical field of impregnation liquid preparation, and particularly discloses water-based polyhydroxy phenolic resin for preparing environment-friendly impregnation liquid and a preparation method of the water-based polyhydroxy phenolic resin. Under a weak acid condition, phloroglucinol and dialdehyde are condensed to prepare the water-based polyhydroxy phenolic resin, and the solid content is 5-13%. The phenolic resin, butadiene-vinylpyridine rubber latex and deionized water are prepared into impregnation liquid, and the solid content is 15-20%. The impregnation liquid does not contain substances harmful to human bodies, such as formaldehyde and resorcinol, and the impregnation liquid is simple in production process, high in production capacity, beneficial to industrial production and relatively good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dipping solution preparation, and specifically discloses an aqueous polyhydroxy phenolic resin for preparing an environmentally friendly dipping solution and a preparation method thereof. Background Art

[0002] Cars are an important means of transportation in today's society, bringing convenience to life. With the rapid development of the automobile industry, the demand for tires, as an important component of automobiles, is also increasing, and higher requirements are also placed on their safety performance.

[0003] On the surface, tires are made of rubber, but in fact, tire rubber is sandwiched with fibers to improve the strength of the tire; and the adhesion between the fiber and rubber is related to the safety of tire use. The polarity difference between fiber and rubber is large, which greatly reduces the adhesion. In order to solve this problem, DuPont developed resorcinol-formaldehyde-latex (RFL) in 1938. Due to its excellent curing speed, it can form a strong adhesive layer in a short time, meeting the high requirements of modern industry for tires.

[0004] Since DuPont developed the RFL dipping system in 1938, this method has been widely used in the field of fiber modification due to its simplicity and effectiveness. However, with the improvement of human health and safety awareness, the toxicity of formaldehyde and resorcinol used in the preparation of RFL dipping solution has aroused widespread concern. In view of the above reasons, it has become imperative to develop a new environmentally friendly dipping system to replace the traditional RFL system, thereby avoiding the use of formaldehyde and resorcinol dipping system.

[0005] Formaldehyde is the first to be considered for replacement. In order to replace the formaldehyde used in the preparation of RFL, Wang JC et al. prepared the HRH dipping system from hydrated silica-resorcinol-hexahydroxymethyl melamine hexamethyl ether and latex, investigated its bonding performance on polyethylene terephthalate (PET) soft wire and nitrile rubber (NBR), and compared it with the RFL dipping system. The results show that the H extraction force of PET soft wire and nitrile rubber treated with HRH reaches 40N, which is 40% higher than the H extraction force (29N) treated with resorcinol-formaldehyde-latex (RFL). However, the hexahydroxymethyl melamine hexamethyl ether used in this method is synthesized from formaldehyde as a raw material, which indirectly uses formaldehyde and complicates the preparation process. Formaldehyde will inevitably be released during the preparation and use of HRH, and its own reactivity is low. Fibers impregnated with HRH are prone to aging, which affects their durability.

[0006] The use of natural environmentally friendly phenolic compounds, such as plant polyphenols, to replace resorcinol has also become a focus of attention. Zhang Bo et al. developed a green and environmentally friendly aramid cord dipping system based on plant polyphenols / polyamines, PTA dipping solution. First, plant polyphenols and polyamines were added to deionized water, adjusted to a pH of 9-11 with sodium hydroxide solution, stirred at room temperature for 60 minutes, and then VP latex was added. The solution was stirred to mix evenly to obtain PTA dipping solution. The results showed that compared with the aramid cord impregnated with RFL dipping solution, the original and heat-aged H extraction force of the aramid cord impregnated with PTA dipping solution was slightly higher, at 174N, reaching the H extraction force level of the aramid cord impregnated with traditional RFL dipping solution and the rubber matrix (168N). Although plant polyphenols are relatively less toxic, they must be extracted from plants, the yield is limited, the structural components are different in each batch, and the composition is unstable; in addition, the structure of the plant polyphenols mentioned is unclear, how to react with polyamines is unclear, and what is generated is unclear, so the practical application value is not great.

[0007] Therefore, the above improved methods cannot actually meet the needs of industrialization, and the preparation process is complicated.

[0008] Nacide NC et al. developed an environmentally friendly polymer resin impregnation solution, which is composed of acrylic resin, epoxy resin, polyisocyanate and rubber latex, and studied the adhesion characteristics of various fibers in this system. Although the research report shows good bonding performance, the interaction mechanism between this mixed resin and fiber and rubber, and between the mixed resins is very complex, the effect is unpredictable, and the improvement and optimization method is difficult to determine. In fact, after the fiber treated with this mixed resin is left for a period of time, its bonding effect with the fiber decreases significantly, which may be due to the hydrolysis and rupture of the ester bond formed by acrylic ester, epoxy resin and fiber. Summary of the invention

[0009] The purpose of the present invention is to overcome the difficulties pointed out in the background technology that the raw materials for preparing the RFL dipping system used in industrial use are highly toxic, the existing environmentally friendly dipping system has poor stability, and the process flow is complicated and cannot meet the needs of practical applications. Provide a preparation method and application method of a water-based polyhydroxy phenolic resin for preparing an environmentally friendly dipping solution with a simple process, environmentally friendly raw materials, and non-toxicity.

[0010] To achieve the above object, the preparation method of the water-based polyhydroxy phenolic resin of the present invention comprises the following steps:

[0011] (1) dissolving phloroglucinol in deionized water and adjusting the pH to 5-6;

[0012] (2) Adding an aqueous solution of a dialdehyde compound to the solution of step (1) and reacting until the aldehyde group is completely reacted, the viscosity of the reaction solution is controlled to be 1.50-4.00 mPa·s, so that the hydroxyl group can be controlled to undergo almost no dehydration reaction.

[0013] In steps (1) and (2), the molar ratio of the dialdehyde compound to phloroglucinol is 1.1 to 1.9:1, preferably 1.2 to 1.6:1.

[0014] The dialdehyde compound is glyoxal, glutaraldehyde, or a mixture thereof; the reaction temperature is 35 to 70° C., preferably 50 to 60° C.; and the reaction time is 1 to 7 hours, preferably 2 to 4 hours.

[0015] (3) Adjust the pH to 7-8.

[0016] The solid content of the water-based polyhydroxyphenol-formaldehyde resin prepared by the above method is 5 to 13%, preferably 6 to 10%.

[0017] The water-based polyhydroxyphenolic resin is used to prepare the dipping solution, which is composed of 33-38% of butylpyrrolidone latex with a solid content of 40±5%, 34-41% of the water-based polyhydroxyphenolic resin with a solid content of 5-13%, and 21-33% of deionized water in weight percentage.

[0018] The preparation method of the dipping solution is as follows:

[0019] (1) Take butylpyrrolidone latex with a solid content of 40±5%, add water-based polyhydroxy phenol-formaldehyde resin with a solid content of 5-13% dropwise, and then add deionized water to adjust the ratio.

[0020] (2) Adjust the pH to 9.5-10.5 with aqueous ammonia; and age at room temperature for 15-20 hours; preferably, the pH is adjusted to 9.5-10; and the ageing time is preferably 16-18 hours.

[0021] Beneficial effects: The water-based polyhydroxyphenolic resin used in the dipping system prepared by the present invention is prepared from phloroglucinol and dialdehyde, and the raw materials overcome the toxicity of formaldehyde and phloroglucinol used in RFL; the resin viscosity and solid content can be consistent with RF resin, which is beneficial to the preparation of the dipping system. The preparation process of the water-based polyhydroxyphenolic resin is controllable, the product structure is controllable, and the repeatability is high; and the prepared water-based polyhydroxyphenolic resin has many active groups, which is beneficial to the connection with fibers and rubber. DETAILED DESCRIPTION

[0022] The present application is exemplified below in conjunction with specific embodiments, but the embodiments are given only as examples and are not considered to be the entire technical solution of the present invention, nor are they intended to limit the overall technical solution of the present invention. Any simple change or replacement of the same or similar technical features shall fall within the scope of protection of the present invention.

[0023] Preparation example of waterborne polyhydroxy phenolic resin:

[0024] Example 1

[0025] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 3.02g (0.024mol) of phloroglucinol and 78.61mL of deionized water were added in sequence, and the solution was stirred under heating until it became clear. The pH was adjusted to 6 with a sodium hydroxide solution with a mass concentration of 11%; the reaction temperature was gradually raised to 65°C, and 5.28g (0.026mol) of a 50% glutaraldehyde aqueous solution was added dropwise, and the dripping was completed in 0.5h, and the temperature was controlled to react for 1h. After cooling to room temperature, the pH of the solution was adjusted to 7 with ammonia water. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 6.72%, and the viscosity was measured to be 1.85mPa·s.

[0026] Example 2

[0027] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 3.04g (0.024mol) of phloroglucinol and 81.41mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 55°C. 5.75g (0.029mol) of a 50% aqueous glutaraldehyde solution was added dropwise, and the solution was allowed to drip for 0.5h. The reaction was controlled at a temperature for 6h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 6.48%, and the viscosity was measured to be 3.88mPa·s.

[0028] Example 3

[0029] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 3.01g (0.024mol) of phloroglucinol and 81.43mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 55°C. 5.74g (0.029mol) of a 50% aqueous glutaraldehyde solution was added dropwise, and the solution was allowed to drip for 0.5h. The reaction was controlled at a temperature for 2h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 6.65%, and the viscosity was measured to be 1.92mPa·s.

[0030] Example 4

[0031] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 3.04g (0.024mol) of phloroglucinol and 94.65mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 55°C. 7.65g (0.038mol) of a 50% aqueous glutaraldehyde solution was added dropwise, and the mixture was dripped over a period of 0.5h. The reaction was controlled at a temperature for 4h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 6.52%, and the viscosity was measured to be 2.36mPa·s.

[0032] Example 5

[0033] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 3.05g (0.024mol) of phloroglucinol and 104.35mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 45°C. 9.14g (0.028mol) of a 50% aqueous glutaraldehyde solution was added dropwise, and the solution was allowed to drip for 0.5h. The reaction was controlled at a temperature for 7h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 6.57%, and the viscosity was measured to be 2.13mPa·s.

[0034] Example 6

[0035] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 3.02g (0.024mol) of phloroglucinol and 68.35mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 65°C. 4.91g (0.034mol) of a 40% aqueous solution of glyoxal was added dropwise, and the mixture was dripped over a period of 0.5h. The reaction was controlled at a temperature for 3h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 7.12%, and the viscosity was measured to be 3.08mPa·s.

[0036] Example 7

[0037] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 3.03g (0.024mol) of phloroglucinol and 78.38mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 55°C. 4.89g (0.034mol) of a 40% aqueous solution of glyoxal was added dropwise, and the mixture was dripped over a period of 0.5h. The reaction was controlled at a temperature for 4h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 6.26%, and the viscosity was measured to be 1.90mPa·s.

[0038] Example 8

[0039] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 6.03g (0.048mol) of phloroglucinol and 95.12mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 55°C. 11.45g (0.057mol) of a 50% aqueous glutaraldehyde solution was added dropwise, and the mixture was dripped over a period of 0.5h. The reaction was controlled at a temperature for 2h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 10.54%, and the viscosity was measured to be 2.72mPa·s.

[0040] Example 9

[0041] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 6.02g (0.048mol) of phloroglucinol and 73.50mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 55°C. 11.47g (0.057mol) of a 50% aqueous glutaraldehyde solution was added dropwise, and the mixture was dripped over a period of 0.5h. The reaction was controlled at a temperature for 2h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxyphenol-formaldehyde resin was 12.95%, and the viscosity was measured to be 3.24mPa·s.

[0042] Comparative Example 1

[0043] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 6.04g (0.048mol) of phloroglucinol and 166.50mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 6 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 55°C. 5.53g (0.057mol) of furfural was added dropwise, and the addition was completed in 0.5h. The reaction was controlled at the temperature for 2h. After cooling to room temperature, ammonia water was added to adjust the pH of the solution to 7. The obtained water-based polyhydroxyphenol-formaldehyde resin had a solid content of 6.5%. The solution was stratified and the viscosity of the solution could not be accurately measured.

[0044] Comparative Example 2

[0045] Into a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 5.52g (0.050mol) of resorcinol and 118.50mL of deionized water were added in sequence, and the mixture was stirred under heating until the solution became clear. The pH was adjusted to 9 with a sodium hydroxide solution having a mass concentration of 11%, and the reaction temperature was gradually raised to 25°C. 8.13g (0.100mol) of a 37% aqueous formaldehyde solution was added dropwise, and the mixture was added over a period of 0.5h. The reaction was then controlled at a temperature for 6h. The solid content of the obtained resorcinol-formaldehyde (RF) resin was 6.49%, and the viscosity was measured to be 1.58mPa·s.

[0046] Table 1

[0047]

[0048] Table 2

[0049]

[0050] Example of preparing environmentally friendly dipping solution:

[0051] Embodiment 11

[0052] Weigh 24.69g, 24.69g, 24.68g, 24.67g, 24.71g, 24.67g, 24.70g, 24.72g, 24.72g, 24.71g, and 24.75g of 40% solid content butyryl latex into 11 100mL beakers and mark them as dipping solutions 1 to 11. 17.72g, 17.72g, 17.74g, 17.69g, 17.73g, 17.70g, 17.74g, 17.71g, 25.21g, 30.30g, 16.71g of deionized water were added to the dipping solutions 1 to 11, and then 26.61g, 26.62g, 26.61g, 26.64g, 26.65g, 26.64g, 26.66g, 26.63g, 13.33g, 13.40g, 26.64g of the water-based polyhydroxyphenolic resin prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were weighed and added dropwise to the dipping solutions 1 to 11; the pH was adjusted to 10 with ammonia water. Ripening was carried out at room temperature for 16 hours. The prepared dipping solutions were observed, and the results were shown in Table 3.

[0053] Table 3

[0054]

[0055] Among the prepared dipping solutions, No. 10 dipping solution broke the emulsion, while the others did not.

[0056] H extraction force test example:

[0057] Example 12

[0058] Dipping and drying: Dipping solution No. 10 could not be dipped due to stratification, so no dipping test was performed. The above dipping solutions 1-9 and 11 were used in sequence to dipping nylon fibers in a continuous method, and then dried. The dipping solution temperature was controlled at 25±3°C, the fiber stayed in the dipping solution for 0.5 seconds, and then dried in an oven at a drying temperature of 130±3°C for 1 minute; 136±2°C for 50 minutes of curing. The impregnated fiber was then stored away from light for subsequent use.

[0059] According to the standard GB / T2942-2009 method, the above-mentioned dipped fibers were used to prepare samples in turn. A 10mm×10mm×10mm rubber strip was used, the vulcanization temperature was 136±2℃, the vulcanization pressure was 3MPa, the vulcanization time was 50min, and the fibers were cooled to room temperature. Eight samples were made for each fiber.

[0060] The H extraction force of the composite material was tested using a universal electronic tensile testing machine in accordance with GB / T2942-2009. During the test, the cord segment was kept vertical, and the tensile test was performed at a speed of 100±10mm / min. The maximum tensile force during the process of the cord being pulled out of the rubber was recorded, and the average value was taken for each group of 8 samples.

[0061] The test results are shown in Table 4:

[0062] Table 4

[0063]

[0064] H extraction force test, the test requirement in the industrial production process is not less than 120N. The results show that the H extraction force of the dipping solution of the present invention meets the industrial requirements, indicating that the nylon fiber and rubber have a good bonding effect, reaching the bonding level of traditional RFL, and can replace the RFL dipping solution. The water-based polyhydroxy phenolic resin used in the present invention does not contain formaldehyde and resorcinol, and has a good application prospect.

Claims

1. A method for preparing a water-based polyhydroxy phenolic resin, characterized in that: The preparation method of the water-based polyhydroxy phenolic resin comprises the following steps: (1) dissolving phloroglucinol in deionized water and adjusting the pH to 5-6; (2) adding an aqueous solution of a dialdehyde compound to the solution of step (1) to allow the aldehyde groups to react fully, and controlling the viscosity of the reaction solution to be 1.50 to 4.00 mPa·s so that the hydroxyl groups do not undergo dehydration reaction; (3) Adjust the pH to 7-8.

2. The method for preparing an aqueous polyhydroxyphenol-formaldehyde resin according to claim 1, wherein: The molar ratio of the dialdehyde compound to phloroglucinol is 1.1-1.9:

1.

3. The method for preparing an aqueous polyhydroxyphenol-formaldehyde resin according to claim 1, wherein: The dialdehyde compound is: glyoxal, glutaraldehyde or a mixture thereof.

4. The method for preparing an aqueous polyhydroxyphenol-formaldehyde resin according to claim 1, wherein: In step (2), the reaction temperature is 35 to 70° C. and the reaction time is 1 to 7 hours.

5. A water-based polyhydroxyphenol-formaldehyde resin prepared according to the method according to any one of claims 1 to 4, characterized in that: The solid content of the waterborne polyhydroxy phenolic resin is 5-13%.

6. An application of a water-based polyhydroxyphenol-formaldehyde resin prepared by the method according to any one of claims 1 to 4, characterized in that: The water-based polyhydroxy phenolic resin is used for preparing an environmentally friendly dipping solution.

7. The use of the water-based polyhydroxy phenolic resin according to claim 6, characterized in that: The composition of the dipping solution by weight percentage is: 33-38% of butylpyrrolidone latex with a solid content of 40±5%, 34-41% of water-based polyhydroxy phenolic resin with a solid content of 5-13%, and 21-33% of deionized water.

8. The use of the water-based polyhydroxy phenolic resin according to claim 6, characterized in that: The preparation method of the dipping solution comprises the following steps: (1) Adding a water-based polyhydroxyphenol-formaldehyde resin having a solid content of 5 to 13% to a butylpyrrolidone latex having a solid content of 40 ± 5%, and then adding deionized water; (2) Adjust the pH to 9.5-10.5 with aqueous ammonia; and mature at room temperature for 15-20 hours.

Citation Information

Patent Citations

  • Improved microcapsules, and production thereof

    CN102438740A

  • High-strength temperature-resistant polyvinyl alcohol gel as well as preparation method and application thereof

    CN116925387A

  • Activated carbon material for vehicles as well as preparation method and application of activated carbon material

    CN117658135A

  • Biomass polyphenol phenolic resin, flame-retardant polyacrylonitrile composite fiber and preparation method of flame-retardant polyacrylonitrile composite fiber

    CN118005867A

  • Resorcinol or phloroglucinol condensation product for aqueous mixture purification

    US4392963A